Prenatal stress and childhood asthma risk: taking a broader view. Issue 2 (February 2016) - Lee, Alison; Wright, Rosalind J.
We now know that asthma risk begins in utero during rapid lung morphogenesis, when the developing fetus is particularly vulnerable to toxic insults due to immature immune, neuroendocrine and antioxidant defences. A meta-analysis published in a recent issue of the European Respiratory Journal (ERJ) [1] builds on substantial evidence highlighting psychological stress as a critical toxic exposure that, starting in utero, can permanently alter interrelated systems ( i.e. immune, autonomic, neuroendocrine and oxidation systems) believed to programme lung growth and consequent respiratory disorders, including asthma [2]. Cumulative evidence confirms stress in pregnancy is a critical prenatal risk for childhood asthma http://ow.ly/W1CCi